Confirmation of inhibitingTLR4/MyD88/NF-κB Signalling Pathway by Duhuo Jisheng Decoction on Osteoarthritis: A Network Pharmacology Approach-Integrated Experimental Study - Liu, Linglong; Xu, Limei; Wang, Shengjie; Wang, Lili; Wang, Xiaoning; Xu, Huifeng; Li, Xihai; Ye, Hongzhi (Frontiers in Pharmacology, 2022)
This study was conducted to identify whether the TLR4/MyD88/NF-κB signalling pathway plays a vital role in osteoarthritis (OA) treatment with Duhuo Jisheng Decoction (DHJSD) on the basis of a network pharmacology approach (NPA)-integrated experiment. Two experiments were conducted as follow: NPA for DHJSD using six OA-related gene series and the key pathway was screened out using NPA. NPA identified a vital role for the TLR4/MyD88/NF-κB signalling pathway in OA treatment with DHJSD, the conventional western blot analysis and qPCR confirmed it. Furthermore, changes of miR-146a-5p and miR-34a-5p in the cellular models were recovered by DHJSD administration, which synergistically contributed to OA therapy. The toll-like receptor signalling pathway and the NF-κB signalling pathway were meaningfully enriched by the miRNA-regulated gene pathways. This study identified and confirmed the TLR4/MyD88/NF-κB signalling pathway is an essential inflammatory signalling pathway in the DHJSD underlying OA treatment. The results provide a basis for further evaluation of the regulatory mechanism of the drug’s efficacy in treating OA.